2014
DOI: 10.1111/bjh.13123
|View full text |Cite
|
Sign up to set email alerts
|

Red blood cell alloimmunization is influenced by recipient inflammatory state at time of transfusion in patients with sickle cell disease

Abstract: SummarySickle cell disease (SCD) patients are at increased risk of red blood cell (RBC) alloimmunization. Recipient inflammatory state at time of transfusion has been shown to regulate alloimmunization in murine models, but evidence is lacking in SCD patients. We retrospectively studied a cohort of alloimmunized SCD patients to determine the influence of pro-inflammatory SCD-related complications at time of transfusion on alloimmunization. For each transfusion, the presence of pro-inflammatory state, degree of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
99
2
8

Year Published

2015
2015
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 187 publications
(110 citation statements)
references
References 36 publications
1
99
2
8
Order By: Relevance
“…A recent study found that the proinflammatory state characteristic of SCD-related challenges, when present at the time of transfusion, was associated with an increased risk of alloimmunization, with acute chest syndrome and vaso-occlusive episodes demonstrating the strongest relationship with alloantibody formation. 35 Although this finding needs replication in prospective studies, it may lend further credence to a preemptive approach aimed at preventing the need for transfusion in the acute setting.…”
Section: Discussionmentioning
confidence: 93%
“…A recent study found that the proinflammatory state characteristic of SCD-related challenges, when present at the time of transfusion, was associated with an increased risk of alloimmunization, with acute chest syndrome and vaso-occlusive episodes demonstrating the strongest relationship with alloantibody formation. 35 Although this finding needs replication in prospective studies, it may lend further credence to a preemptive approach aimed at preventing the need for transfusion in the acute setting.…”
Section: Discussionmentioning
confidence: 93%
“…The observed difference may have been underestimated as the interval between transfusion and antibody screening was much larger in the episodic group and under detection of antibodies due to evanescence may have occurred [49,50]. In general, episodic transfusions are often given for treatment of acute pro-inflammatory complications such as an acute chest syndrome, or hemolytic or vasoocclusive crises [3,24,51]. The higher alloimmunization risk associated with episodic transfusions adds to the notion that RBC units given during acute, inflammatory events are associated with an increased risk for alloimmunization [24,52,53].…”
Section: Discussionmentioning
confidence: 99%
“…In general, episodic transfusions are often given for treatment of acute pro-inflammatory complications such as an acute chest syndrome, or hemolytic or vasoocclusive crises [3,24,51]. The higher alloimmunization risk associated with episodic transfusions adds to the notion that RBC units given during acute, inflammatory events are associated with an increased risk for alloimmunization [24,52,53].…”
Section: Discussionmentioning
confidence: 99%
“…However, in SCD patients, a recent study showed that an inflammatory state at the time of transfusion, independently of direct TLR stimulation, can influence RBC alloimmunization. 24 The underlying inflammatory state of the patient and TLR signaling may, therefore, be central to the process of RBC alloimmunization.…”
mentioning
confidence: 99%